Glavne ali kardinalne kreposti bl. Antona Martina Slomška - Turnšek, Marjan (Edinost in dialog, 2023)
This paper presents Blessed Anthony Martin Slomšek as a man who led an above-average virtuous life. The author presents Slomšek concretely in the exercise of the main or cardinal virtues of prudence (wisdom), justice, cordiality and temperance throughout his life. He also shows their gradual growth. In the process of Slomšek's beatification, the extraordinary influence of Slomšek's personality became clear, as other people were drawn to him as a kind of »incandescence« for these virtues. Slomšek's extraordinary pastoral zeal was not only based on theoretical teaching but also rooted in a personally lived life of the cardinal virtues, which shaped him into an extremely harmonious and positive personality. Given the gradual resurgence of interest in the virtues in both ethics and morality, it is very appropriate to present and examine Slomšek's virtuous life
Keywords: cardinal virtues; cordiality; justice; kardinalne kreposti; kreposti; modrost; pravičnost; prudence; razumnost; Slomšek, Anton Martin; srčnost; temperance; virtues; wisdom; zmernost